TRIM E3 ligases interfere with early and late stages of the retroviral life cycle. - Pradeep D Uchil (Public Library of Science (PLoS), 2008)
Members of the TRIpartite interaction Motif (TRIM) family of E3 ligases have been shown to exhibit antiviral activities. Here we report a near comprehensive screen for antiretroviral activities of 55 TRIM proteins (36 human, 19 mouse). We identified approximately 20 TRIM proteins that, when transiently expressed in HEK293 cells, affect the entry or release of human immunodeficiency virus 1 (HIV), murine leukemia virus (MLV), or avian leukosis virus (ALV). While TRIM11 and 31 inhibited HIV entry, TRIM11 enhanced N-MLV entry by interfering with Ref1 restriction. Strikingly, many TRIM proteins affected late stages of the viral life cycle. Gene silencing of endogenously expressed TRIM 25, 31, and 62 inhibited viral release indicating that they play an important role at late stages of the viral life cycle. In contrast, downregulation of TRIM11 and 15 enhanced virus release suggesting that these proteins contribute to the endogenous restriction of retroviruses in cells.